Molecular and dissociative adsorption of oxygen on au-pd bimetallic clusters: role of composition and spin state of the cluster - Dar, Manzoor Ahmad; Krishnamurty, Sailaja (Acs Omega, 2019)
Utilization of molecular oxygen as an oxidizing agent in industrially important reactions is the ultimate goal to design environmentally benign processes under ambient conditions. However, the high thermal stability and a large O-O dissociation barrier in O-2 molecule pose a great challenge toward its successful application in the oxidative chemistry. To achieve this goal, different catalysts based on monometallic and bimetallic clusters have been developed over the years to promote binding and dissociation of molecular oxygen. The successful design of efficient metal cluster catalysis needs an in-depth knowledge of synergistic effects between different metal atoms and intrinsic catalytic mechanisms for O-2 adsorption and dissociation. Here, we present a systematic theoretical investigation of reaction pathways for O-2 adsorption and dissociation on Au-8, Pd-8, and Au8-nPdn (n = 1-7) nanoclusters in different spin states. The density functional calculations point out that the O-2 dissociation barriers can be significantly reduced with the help of certain bimetallic clusters along specific spin channels. Our results particularly indicate that Au5Pd3 and Au1Pd7 show very large O-2 binding energies of 1.76 and 1.69 eV, respectively. The enhanced O-2 binding subsequently leads to low activation barriers of 0.98 and 1.19 eV along the doublet and quartet spin channels, respectively, without the involvement of any spin flip-over for O-2 dissociation. Furthermore, the computed O-2 dissociation barriers are significantly low as compared to the already reported barriers (1.95-3.65 eV) on monometallic and bimetallic Au-Ag clusters. The results provide key mechanistic insights into the interaction and dissociation of molecular oxygen with Au-Pd clusters, which can prove informative for the design of efficient catalysts for oxidative chemistry involving molecular oxygen as a reactant.

Surface functionalization: an efficient alternative for promoting the catalytic activity of closed shell gold clusters - Joshi, Krati; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Physical Chemistry Chemical Physics, 2020)
{Surface functionalization through adsorption of ligands or non-metal atoms is considered to be an interesting and viable approach for tuning the physicochemical properties of gold clusters. Highly stable and magic numbered electronic configurations of thiolate protected gold clusters such as Au-25(SR)(18), Au-38(SR)(24)etc. with intriguing properties are the direct manifestation of the rich chemistry of the Au-S interface. The present investigation discerns the CO oxidation activity of structurally well characterized sulphur functionalized gold cluster anions AumS4-

Electrocatalytic nitrogen reduction directed through the p-band center of boron on BSAC@Mo2C - Maibam, Ashakiran; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Materials Advances, 2021)
Greener modes of ammonia synthesis via the electrocatalytic route have been investigated on pristine and defective Mo2C based monolayers anchored with metal-free boron atom catalysts. Boron single atom catalysts (SACs) on the defective Mo2C monolayer has been found to activate N2 strongly with an adsorption energy of −1.92 eV and reduce it to NH3 efficiently with a significantly low overpotential of 0.41 eV. The exothermic adsorption of N2 and low overpotential for the nitrogen reduction reduction (NRR) appertain to the p-band center of the boron atom catalyst and charge transfer between the adsorbed N2 and the catalyst, respectively. This work brings forth the correlation between electron occupancy on the boron center and NRR catalytic efficiency on a metal-free SACs@Mo2C monolayer couple, thereby serving as a lead in designing metal free electrocatalysts for the NRR.

Exploring the structure and electronic properties of germanium doped boron clusters using density functional theory based global optimization method - Anis, Insha; Dar, Mohd Saleem; Rather, Ghulam Mohammad; Dar, Manzoor Ahmad (New Journal of Chemistry, 2022)
Density functional theory calculations in the framework of B3LYP, TPSS and M06-L were carried out to investigate the effect of single and double germanium atom doping on the geometric structure and electronic properties of boron clusters with 10 to 20 atoms. Global minima of GeBn and Ge2Bn (n = 10-20) were first obtained through Crystal Structure Analysis by the Particle Swarm Optimization method and then subsequently optimized using meta-generalized gradient approximation, hybrid and local functionals. It is found that the lowest energy structures of GeBn and Ge2Bn clusters exhibit planar, quasi-planar, semi-cage, bowl, and double ring topologies. Like BnSi clusters, the results reveal that the germanium atom prefers the peripheral regions of the B-n framework contrary to transition metal doped boron clusters. Furthermore, the calculated electronic properties such as the average binding energy and second order difference in binding energy indicate GeB20 and Ge2B16 to be the most stable clusters. Molecular orbital and adaptive natural density partitioning analyses were carried out to understand the extra stability of GeB20 and Ge2B16 clusters.

First-principles investigation of the electrocatalytic reduction of CO2 on zirconium-based single-, double-, and triple-atom catalysts anchored on a graphitic carbon nitride monolayer - Hassan, Afshana; Anis, Insha; Shafi, Sadaf; Assad, Assif; Rasool, Anjumun; Khanam, Romana; Bhat, Gulzar Ahmad; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (ACS Applied Nano Materials, 2022)
Conversion of carbon dioxide (CO2) with the help of an appropriate electrocatalyst with high stability, low onset potential, and exceptional selectivity is still one of the great tasks in the electrocatalytic reduction of CO2 to valuable chemicals. Herein, by means of systematic first-principles simulations, we investigate the CO2 reduction reaction (CO2RR) activity of zirconium-based single-, double-, and triple-atom (Zrn@C2N; n = 1-3) catalysts anchored on a graphitic carbon-nitride monolayer. In tune with the Sabatier principle, our results reveal that a moderate CO2 binding is vital for a low onset potential for the CO2RR. Consequently, based on rigorous free energy calculations, the Zr-based single-atom catalyst (SAC) is found to be most effective to convert CO2 to valuable products such as HCOOH and CH3OH. It is worth noting that CO2 reduction to HCOOH is spontaneous via the *HCOO intermediate on Zr1@C2N and involves a low onset potential of -0.23 V with respect to the reversible hydrogen electrode from the *COOH intermediate. Among all the catalysts evaluated computationally, the Zr SAC further reveals the lowest onset potential of -0.89 V for CH3OH formation. The results show that the Zr-based catalysts especially Zr1@C2N are found to effectively suppress the competitive hydrogen evolution reaction and promote the CO2RR. Moreover, all three catalysts exhibit high kinetic and thermal stability with negligible distortion due to which their structures can be retained very well up to 600 K. Thus, the current work may provide effective catalyst-design strategies for enhancing the electrocatalytic CO2RR performance of Zr-based materials.
Keywords: C1 and C2 products; CO2 reduction; first-principles simulations; hydrogen evolution reaction; onset potential; single-atom catalysts (SACs); Zrn@C2N catalysts

Probing the site-specific reactivity and catalytic activity of Ag-n (n=15-20) silver clusters - Anis, Insha; Dar, Mohd Saleem; Bhat, Gulzar Ahmad; Rather, Ghulam Mohammad; Dar, Manzoor Ahmad (ACS Omega, 2022)
Density functional theory calculations within the framework of generalized gradient approximation (GGA), meta-GGA, and local functionals were carried out to investigate the reactivity and catalytic activity of Ag-n (n = 15-20) clusters. Our results reveal that all the Ag-n dusters in this size range, except Ag-20, adsorb O-2 preferably in the bridged mode with enhanced binding energy as compared to the atop mode. The O-2 binding energies range from 0.77 to 0.29 in the bridged mode and from 0.36 to 0.15 eV in the atop mode of O-2 adsorption. The strong binding in the case of the bridged mode of O-2 adsorption is also reflected in the increase in O-O bond distance. Natural bond orbital charge analysis and vibrational frequency calculations reveal that enhanced charge transfer occurs to the O-2 molecule and there is significant red shift in the stretching frequency of O-O bond in the case of the bridged mode of O-2 adsorption on the clusters, thereby confirming the above results. Moreover, the simulated CO oxidation reaction pathways show that the oxidation of the CO molecule is highly facile on Ag-16 and Ag-18 clusters involving small kinetic barriers and higher heats toward CO2 formation.

Tantalum based single, double, and triple atom catalysts supported on g-C2N monolayer for effective nitrogen reduction reaction: a comparative DFT investigation - Rasool, Anjumun; Anis, Insha; Dixit, Mudit; Maibam, Ashakiran; Hassan, Afshana; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Catalysis Science & Technology, 2022)
Design of efficient and low cost electrocatalysts for the reduction of N-2 molecule to NH3 in a green manner remains a great challenge in the 21st century. Herein, we have used density functional theory based first principle simulations to systematically investigate the nitrogen reduction reaction (NRR) ability of single, double, and triple Ta-atom catalysts anchored to C2N monolayer. Our results demonstrate that the single and triple Ta-atom catalysts anchored to C2N monolayer act as superior catalysts for the NRR via alternating and distal pathways as compared to the Ru(0001) stepped surface. In particular, the triple Ta-atom catalyst anchored to C2N shows enhanced NRR performance with a limiting potential of -0.72 V which is comparable to the experimentally reported Ru based single atom catalyst. Further, all the three catalysts were found to be highly selective for NRR with an enhanced ability to suppress the competitive hydrogen evolution reaction. Electronic structure analysis revealed that the enhanced ability of Ta-3@C2N catalyst to effectively capture and reduce N-2 molecule could be attributed to the built up of localized d states near the fermi level, thereby aiding in strong electron transfer into the antibonding orbitals of N-2. Thus, our findings propose a highly active catalyst for the NRR with an emphasis on the importance of triple atom-based catalysts for electrocatalytic applications.

Computational identification of most potent atom pair catalysts for electrocatalytic nitrogen reduction reaction over hydrogen evolution reaction - Verma, Tushar Singh; Dar, Afshana Hassan; Dar, Manzoor Ahmad; Selvaraj, Kaliaperumal; Krishnamurty, Sailaja (Inter., 2024)
Robust electrocatalytic atom pair compositions (APCs) where Nitrogen Reduction Reaction (NRR) is more enhanced over competing Hydrogen Evolution Reaction (HER) is searched for using computational studies based on Density Functional Theory based methods. Atomic pairs are anchored on mechanically and thermally stable graphene surfaces. A wide range of transition metal based atom pair compositions from 3d, 4d, and 5d groups are systematically investigated for reduction of dinitrogen molecule with lower reduction barrier as compared to HER. APR compositions of Ni-Rh with an overall limiting potential of -0.22 V, Fe-W with an overall limiting potential of -0.26 V and Co-Pt with an overall limiting potential of -0.28 V are identified as the most potent atomic pairs for enhanced nitrogen reduction reaction over the HER. Finally, the performance of most potent composition, viz., Ni-Rh is validated to be consistent with respect to their thermodynamic stability and performance within the solvent effects.
Keywords: Atom pair catalysts; Density Functional Theory (DFT); Electrochemical nitrogen reduction reaction (eNRR); hydrogen evolution reaction (HER); IR stretching frequencies; N-N bond length

Size and morphology dependent activity of Cu clusters for CO2 activation and reduction: a first principles investigation - Amin, Seerat; Krishnamurty, Sailaja; Dar, Manzoor Ahmad; Joshi, Krati (ChemPhysChem, 2024)
Various Cu-based materials in diverse forms have been investigated as efficient catalysts for electrochemical reduction of CO2; however, they suffer from issues such as higher over potential and poor selectivity. The activity and selectivity of CO2 electro reduction have been shown to change significantly when the surface morphology (steps, kinks, and edges) of these catalysts is altered. In light of this, size and morphology dependent activity of selected copper clusters, Cun (n=2-20) have been evaluated for the activation and reduction of CO2 molecule. The phase-space of these copper clusters is rich in conformations of distinct morphologies starting from planar, 2D geometries to prolate-shaped geometries and also high-symmetry structures. The binding efficiency and the activation of CO2 are highest for medium sized clusters (n=9-17) with prolate-morphologies as compared to small or larger sized CunCO(2) clusters that are existing mainly as planar (triangular, tetragonal etc.) or highly-symmetric geometries (icosahedron, capped-icosahedron etc.), respectively. The best performing (prolate-shaped) CunCO2 conformations are quite fluxional and also they are thermally stable, as demonstrated by the molecular dynamics simulations. Furthermore, on these CunCO(2) conformations, the step-by-step hydrogenation pathways of CO2 to produce value-added products like methanol, formic acid, and methane are exceptionally favorable and energy-efficient.
Keywords: CO2 activation; CO2 hydrogenation; Copper clusters; Density Functional Theory (DFT); molecular dynamics

Boosting the CO2 reduction activity of Cu double-atom catalysts through coordination environment engineering - Amin, Seerat; Krishnamurty, Sailaja; Dar, Manzoor Ahmad (Sustainable Energy & Fuels, 2025)
Double-atom catalysts (DACs) offer a reasonable and scalable route towards carbon neutrality owing to their efficient catalytic features. However, the challenges associated with the flexibility of their coordination structure usually restrict their full potential as efficient catalysts. Herein, we comprehensively examined the impact of coordination environment regulation on the CO2R activity of Cu2-DACs supported on C, N, or B co-doped graphene using ab initio simulations. We highlighted the marked role of the local coordination sphere of Cu2-DACs in modulating their structural stability and charge transfer characteristics, thereby regulating the adsorption of CO2 and various reaction characteristics. Notably, boron- and carbon-coordinated Cu2 centres (Cu2-BxCy) resulted in remarkably strong CO2 adsorption (-0.65 to -2.31 eV), attributed to their amplified electronic interactions with the CO2 molecule. The weak CO2 binding observed on the carbon-nitrogen- and nitrogen-boron-coordinated Cu2 centres (Cu2-NxCy and Cu2-NxBy) further highlighted the role of the coordination environment in facilitating the versatile binding modes of the key reaction species. The varying CO2 interactions in these systems were further comprehended and supported by a multilevel descriptor () combining both geometric and electronic parameters. This descriptor closely mirrored the DFT results, thereby accentuating its effectiveness as a predictive tool to perfectly model the CO2 interactions on these catalysts. Moreover, the dynamic behaviour in the adsorption modes led to partial breakdown of the conventional linear scaling relations between the key CO2 reduction intermediates (*COOH, *CO, and *HCO). Among the numerous types of investigated electrocatalysts, Cu2-B5C1 emerged as a highly active and selective catalyst for methanol production, with a remarkably low limiting potential of -0.54 V, surpassing the performance of several reported Cu-based systems. Besides, our findings underscored the often-overlooked yet crucial role of explicit solvation, which significantly altered both the potential-determining step and product selectivity. These outcomes emphasized the necessity of including solvation effects in realistic electrochemical modelling. Collectively, this study provides a critical mechanistic insight into better understanding the coordination effect on the CO2R and a robust design strategy for next-generation Cu-based DACs, guiding the development of highly efficient and selective catalysts for CO2 electroreduction.